SADISTIC INNOCENCE IN JAUME COLLET-SERRA'S ORPHAN (2009): A PSYCHOANALYTIC PERSPECTIVE - WIDYASTUTI , FARIDA AYU (2011)
This study attempts to explore the sadistic innocence of the major character on her live. The objective of the research is to analyze the major character based on its structural elements and psychoanalytic perspective. In analyzing the psychoanalytic aspects, the researcher applies the theory of psychoanalysis proposed by Sigmund Freud. The researcher employs the qualitative research as a type of the research. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the Orphan movie directed by Jaume Collet-Serra released in 2009. While the secondary data sources are other materials taken from books, journal, and internet related to the study. The results of this study are as follows. Firstly, the structural elements the movie presents a unity. It appears in the beginning, middle and end of the story. Secondly, the psychoanalytic analysis shows the phenomenon of sadism behind the innocence face from the major character. Finally, the psychoanalytic analysis shows that sadism may be hidden behind innocence appearance.